Interpretation of Verses about Plants in the Qur'an: A Review of Ma'ānī, Bayān, and Sufism - Irsad, Nursalim; Taufiq, Wildan; Fathurrohman, Asep Ahmad (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
The study of the Qur'an's verses that discuss plants reveals not only the beauty of God's creation but also contains profound theological, aesthetic, and spiritual messages. This article analyzes these verses through the approach of balaghah science, specifically ma'ānī and bayan, and enriches their inner meaning with a Sufi perspective. Ma'ānī science is used to examine the structure and style of language that emphasizes certain meanings, while bayan science reveals the meaning of figures of speech such as tashbīh, isti'ārah, and kināyah. And the Sufi approach views plants as symbols of tajallī Allah, the human spiritual journey, and a means of contemplation towards ma'rifatullāh. The process of plant growth is interpreted as an allegory of the development of faith, love, and good deeds that must be cultivated through spiritual training. The research findings demonstrate that plants in the Quran are not merely biological objects, but rather a medium of divine communication that conveys the values ​​of monotheism, beauty, and ecological awareness. Thus, this multidisciplinary interpretation presents a holistic and transformative understanding of the Quran.